DATA ACTIVISM AND COVID-19 IN INDONESIA - Ibnu Nadzir (Jurnal Kependudukan Indonesia, 2020)
The governmentâ€™s inability to provide information in relation to COVID-19 in Indonesia, has stimulated grassroots efforts from society to develop data activism. These are the kind of activism that proliferates from modern social media ecosystem and utilizes data as the core of their movement. The article proposes that there are at least three forms of activism differentiated based on the actors, their main sources of data, and characteristic. These forms of activisms are aimed to provide data and information that could help both government and society to better mitigate the impact of pandemic. While data activism provides some hope among other grim outlook of COVID-19 management in Indonesia, the questions on its impacts are still looming under the contested authorities of information in Indonesia.Â